Stem Cell Heterogeneity of Mononucleated Cells from Murine Peripheral Blood: Molecular Analysis - Muhammad Dain Yazid; Shahrul Hisham Zainal Ariffin; Sahidan Senafi; Zaidah Zainal Ariffin; Rohaya Megat Abdul Wahab (The Scientific World Journal)
The main purpose of this paper was to determine the heterogeneity of primary isolated mononucleated cells that originated from the peripheral blood system by observing molecular markers. The isolated cells were cultured in complete medium for 4 to 7 days prior to the separation of different cell types, that is, adherent and suspension. Following a total culture time of 14 days, adherent cells activated the Cd105 gene while suspension cells activated the Sca-1 gene. Both progenitor markers, Cbfa-1 and Ostf-1, were inactivated in both suspension and adherent cells after 14-day culture compared to cells cultured 3 days in designated differentiation medium. In conclusion, molecular analyses showed that primary mononucleated cells are heterogeneous, consisting of hematopoietic stem cells (suspension) and mesenchymal stem cells (adherent) while both cells contained no progenitor cells.